Bacterial contamination of enteral feeds. Issue 4 (April 1994) - Patchell, C J; Anderton, A; MacDonald, A; George, R H; Booth, I W
Abstract : Enteral nutrition is increasingly used to provide nutritional support for children in hospital and at home. No suitable formula is available for preschool children, however, and until recently a modular feed has been prepared. The hypotheses were examined that the use of a modular feed is associated with increased bacterial contamination, and that contamination is more common in the home than in hospital. Thirty five children receiving enteral nutrition initially in hospital and subsequently at home were allocated randomly to receive either a modular feed or a newly available sterile ready to use paediatric feed. Samples of feed were taken from the nutrient container immediately after filling and at the end of feeding. The results show that feed contamination is common in hospital and at home, but significantly more so at home. The data indicate the importance of hygiene training for parents and the desirability of a ready to use formula.